Selective and vertical microfabrication of lipid tubule arrays on glass substrates using template-guided gentle hydration - Park, Min Cheol; Sukumar, Pavithra; Kim, Sang Kyung; Kang, Ji Yoon; Manz, Andreas; Kim, Tae Song (Royal Society of Chemistry, 2016)
Generally, asymmetric tubular lipid structures have been formed under the specific condition of gentle hydration or by using hydrodynamic and/or electrical elongation of vesicular lipid structures. Small-size lipid tubes are, however, very difficult to allocate or align in the vertical direction on the specific site of the substrate and, therefore, the ability to produce them selectively and in large quantities as an array form is limited. Herein, we propose an easy and novel method to fabricate selective and vertical lipid tube arrays using template-guided gentle hydration of dried lipid films without any external forces. A lipid solution was drop-dispensed onto a porous membrane and dried to form a lipid film. Then, the lipid-coated porous membrane was transferred to a glass substrate by using a UV-cured polymer layer to achieve tight bonding. Upon swelling with an appropriate buffer, expansion forces due to osmotic pressure during the gentle hydration process were highly constrained to confined pores, thereby resulting in the nucleation of tube-like lipid structures through the pores. Interestingly, according to the aspect ratio of pores (AR(pore), pore length/pore diameter), different shapes of lipid structures, including vesicular, oval, and tube-like, were generated, which indicates the importance of the ARpore, as well as the pore diameter, during fabrication of tubular lipid structures. Also, this approach was easily modified with 1% chitosan to enhance the stability of the lipid tubes (>30 min in life time), by lipid coating twice and by using unsaturated lipids to increase tube length (>30 mu m in length). Therefore, in the future, the simple but robust template-guided gentle hydration method will be a useful tool for fabricating addressable and engineered lipid tube arrays as a sensory unit.
Keywords: GIANT UNILAMELLAR VESICLES; PHOSPHOLIPID-VESICLES; ELECTRIC-FIELD; ELECTROFORMATION; LIPOSOMES; MEMBRANES; TUBES; CHITOSAN; INSIGHTS; SINGLE